A Multivariate Approach for the Treatment of Mixed Anodizing Coating Wastewater by Electrochemical Processes - Turk, Oruc Kaan; Turk, Tugce Tarhan; Guvenc, Senem Yazici; Cakmakci, Mehmet (WILEY, 2025)
This research examined the treatment of mixed wastewater generated by the anodizing coating industry through electrocoagulation (EC) and electrooxidation (EO) processes. Key operational parameters, initial pH, applied current, and electrolysis time, were systematically varied to optimize contaminant removal. Process optimization was conducted using the Box-Behnken design (BBD), and the statistical validity of the model fit was assessed via analysis of variance (ANOVA). The responses for the EC and EO processes were chemical oxygen demand (COD), aluminum (Al), and sulfate removal efficiencies. The correlation coefficients (R 2) for all model responses exceeded 0.95, demonstrating a strong agreement between predicted and observed values. Validation experiments confirmed high pollutant removal efficiencies, with COD removal rates of 94.5% and 90.8%, Al removal rates of 98.5% and 92.0%, and sulfate removal rates of 85.0% and 72.0% for the EC and EO processes, respectively. Although both procedures successfully accomplished effective pollutant removal, the EO method did not meet the discharge standards for the sewerage system, particularly in relation to sulfate concentration These findings highlight the superior efficacy of the EC process in sulfate removal, particularly for mixed wastewater from the anodizing coating industry.
Keywords: anodizing coating industry wastewater; BBD; electrocoagulation; electrooxidation; sulfate removal; RESPONSE-SURFACE METHODOLOGY; BORON-DOPED DIAMOND; ADVANCED OXIDATION PROCESSES; SYNTHETIC ORGANIC-DYES; HEAVY-METAL IONS; ELECTROCOAGULATION TREATMENT; TEXTILE WASTEWATERS; REMOVAL; OPTIMIZATION; ANODE; Engineering; Environmental Sciences & Ecology; Marine & Freshwater Biology; Water Resources